Age of onset effects in child bilingual acquisition : identifying the turning point - Sopata, Aldona; Długosz, Kamil (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study investigates the effects of age of onset of acquisition (AO) and two other factors, chronological age of participants and language input, on sentence repetition performance. We focus on identifying the turning point for the effect of AO. Our analysis concerned sentence repetitions in German of 58 bilingual Polish-German children. The main findings were that AO and chronological age rather than cumulative input were significant predictors of correctness in the performance of bilingual children at an advanced stage of acquisition. Using receiver operating characteristic curve analysis, this paper demonstrates that the AO at 36.5 months is the optimal cut-off point to predict the general and morpho-syntactic correctness of repeated sentences. We conclude then that onset of acquisition at the age of 3 years should be identified as the boundary between first language and early child second language acquisition in the morpho-syntactic domain.